Program Istruktur Kebugaran Jasmani - Dedi Supriadi; Akhmad Olih Solihin; Bangbang Syamsudar; Henry Asmara; Sony Hasmarita; Awan Suryawana (STKIP Pasundan, 2024)
Program pengabdian kepada masyarakat yang berjudul